The effects of trust in Brazilian PNPs: interpersonal and interorganizational trust in the cultural sector social organizations in São Paulo, Brazil - Oquendo, Mirtha Iris (2012)
This study seeks to evaluate how enterorganizational and interpersonal trust affects the degree of State interference in the operations of public-nonprofit partnerships (PNPs). We conducted a qualitative case study in two Brazilian PNPs, Projeto Guri and Orquestra Sinfônica do Estado de São Paulo, through documental analysis and semi-structured interviews. Content analysis of the data yielded a trust framework that begins to explain how a variety of factors, including the protective qualities of the management contract and the strength of the board, moderate the relationship between interpersonal and interorganizational trust in PNPs. The study reveals that unlike Zaheer et al (1998), interpersonal trust had a unique and prominent effect on State interference and types of collaboration in PNPs. Parting from the suggestions by previous authors to contextualize PNP literature findings, the framework takes into account the highly personalistic qualities of Brazilian culture as well as historical and institutional context while highlighting the crucial role of interpersonal trust in Brazilian PNPs.